Elevated carbohydrate antigen 125 (CA125) is associated with incident heart failure and mortality in acute coronary syndrome - Troels Yndigegn; Thomas Gu; Helena Grufman; David Erlinge; Arash Mokhtari; Ulf Ekelund; Martin Magnusson; Emma Gustafsson; Jan Nilsson; Isabel Goncalves; Alexandru Schiopu (ESC Heart Failure)
Abstract Aims Carbohydrate antigen 125 (CA125), a mucin produced by serosal cells in response to mechanical and inflammatory stimuli, has emerged as an important biomarker to guide risk stratification in heart failure (HF). The prognostic value of CA125 in acute coronary syndrome (ACS) patients is less explored. Methods In a cohort of 524 ACS patients (73% males, mean age 67 ± 12 years), we assessed the associations between CA125 and the risk for HF and death during a median follow‐up period of 27.3 months for incident HF and 39.5 months for mortality. Plasma CA125 was measured within 24 h after admission in the entire cohort and after 6 weeks in a subgroup of 115 elderly patients (>75 years of age). We also assessed the relationships between baseline CA125 and echocardiographic parameters of cardiac structure and function at 1 year post‐ACS in this subgroup. Results Baseline CA125 was associated with incident HF in the entire cohort in a Cox proportional hazards model adjusted for age, sex, cardiovascular (CV) risk factors (diabetes, smoking, hypertension, previous HF, previous ACS and previous stroke), renal function and revascularization {hazard ratio [HR] 1.46 [95% confidence interval (CI) 1.10–1.93] per 1‐standard deviation [SD] CA125 increase; P = 0.009}. In the detailed follow‐up subgroup, elevated baseline CA125 predicted subsequent deterioration of left ventricular (LV) ejection fraction (LVEF), defined as a >5% absolute LVEF decrease in patients with LVEF ≥ 50% at discharge [odds ratio (OR) 3.31 (95% CI 1.15–9.54) per 1‐SD baseline CA125 increase; P = 0.027]. We also found significant correlations between high baseline CA125 and larger LV volumes (LV end‐diastolic volume index, Spearman's r = 0.329, P < 0.001; LV end‐systolic volume index, r = 0.391, P < 0.001) and left atrial volume index (r = 0.320, P < 0.001) at 1 year post‐ACS, indicative of adverse cardiac remodelling. Elevated baseline and follow‐up CA125 were associated with increased mortality, independently of age and sex [HR 1.37 (95% CI 1.09–1.71), P = 0.006, per 1‐SD baseline CA125; HR 1.98 (95% CI 1.06–3.67), P = 0.031, per increasing 6 week CA125 tertile]. The relationship between 6 week CA125 and incident mortality remained significant in the fully adjusted model [HR 2.23 (95% CI 1.15–4.35) per increasing CA125 tertile; P = 0.018]. Conclusions We report independent associations between elevated CA125, LV dysfunction, cardiac remodelling, incident HF and mortality post‐ACS. Our results warrant further evaluation of CA125 as a potential biomarker for risk stratification and management of ACS patients, both at the time of the acute coronary event and during follow‐up.